Managing Safety Risks at Uncontrolled Rail Crossings: The Case of JPL 87 KM 29+745 in Bekasi City - Nurhadi, Muhamad; Astuti, Septiana Widi; Suryandari, Mega; Dewi, Puspita; Yuanda Patria Tama (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2025)
A level crossing is an intersection between a road and a railway line where the intersection is in a horizontal plane. To improve safety in railway operations, it is necessary to monitor both infrastructure, facilities, traffic and human resources. The level of safety is the main factor that is taken into consideration by service users when choosing the mode of transportation to use. Whether on land, sea or air, safety always comes first. Safety is an absolute factor that must be present in every situation, including rail transportation itself. There needs to be collaboration between parties to achieve safety at level crossings. Every level crossing has certain risks. Risk cannot be eliminated, but can be controlled. Risk control is the process of responding to and treating risks, as well as follow-up plans (Hanafi, 2006). It is necessary to identify risks as a basis for steps that must be taken by the relevant parties so that they can be controlled to reduce accidents at level crossings.